Inferring the Unknown: Enacting Organic Standards through Certification - Van der Kamp, Maarten (The International Journal of Sociology of Agriculture and Food, 2013)
In the food and agricultural sector, third-party certification has become a prominent mechanism to organize markets for ‘sustainable’ products. Yet, to date the everyday activities through which this is achieved have not been examined. Based on my empirical study of the reproduction of the standards for organic agriculture in the UK, I develop an account of certification practice. I conceptualize the knowledge object of the certification process as having epistemic dimensions that are allowed to unfold for limited periods of time. I argue that there is a systemic absence of knowledge in the certification process, and that the resulting uncertainty in the process cannot be resolved. However, paralysis in the process and arbitrary decision-making are avoided through standardized procedures. I argue that in third-party certification the discretionary space to find interpretations of standards has shifted from farmers to certification bodies. I suggest that this space is highly formalized and documented in response to the inherent uncertainty of certification. I suggest that ‘sustainability’ standards are continually rewritten in the certification process and that therefore they are alive. The everyday activities of certifying licensees enable the circulation of the knowledge objects of different licensees through which the enactments of licensees become connected. I argue that this formalizes and strengthens the uniformities across time and space that are constructed through standards. I conclude that certification is not mere observation but that it actively shapes how ‘sustainability’ standards are enacted in farming practice.